If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 8 = -25 Reorder the terms: 8 + y = -25 Solving 8 + y = -25 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + y = -25 + -8 Combine like terms: 8 + -8 = 0 0 + y = -25 + -8 y = -25 + -8 Combine like terms: -25 + -8 = -33 y = -33 Simplifying y = -33
| 16-(3x+20)=(17-2x)-15 | | 18x-9=9x+3 | | 4p+3g=395 | | -(8-2x)=32 | | 7+25x=20x+10 | | X*0.05=6 | | -(8x-2x)=32 | | 3(x+2)+2x=2(x-7)+2x+5 | | 12y-32=-15 | | 82-(-3)= | | 12y-32=-35 | | -21-(-24)= | | x-24=2x+5 | | 8n^2=24n | | 6x+9=-72-6x | | 24*6x=9-9x | | n^2+w=12 | | x-3.75=12.25 | | z=2x-7y | | 6(x+31)=216 | | 1/3p=12 | | 5x=1+2y | | -x+8=6 | | X/2-4-6 | | 10x-68=-8 | | 6(2/3x-10) | | 7x-4=22-x | | 10+4x=4+x | | -7x-9=-30 | | -6x+9=-3 | | (2y-3)(3y+5)= | | 2x+5=7 |